Answer:
Step-by-step explanation:
given that the annual consumption of beef per person was about 64.9 lb in 2000 and about 60.7 lb in 2007.
Assume B(t), the annual beef consumption t years after 2000, is decreasing according to the exponential decay model
i.e. [tex]B(t) = B_0 e^{-kt}[/tex], where t is the number of years from 2000
B0 = quantity in 2000 = 64.9
So the equation is
[tex]B(t) = 64.9 e^{-kt}[/tex]
When t =7, B(7) = 60.7
Substitute to solve for k
[tex]60.7 = 64.9 e^{-7k}\\\\e^{-7k}=0.9353\\k =0.009557[/tex]
So equation woul dbe
[tex]B(t) = 64.9e^{-0.0096t}[/tex]
c) B(t) = 30 gives
[tex]30= 64.9e^{-0.0096t}\\t = 80.38[/tex]
i.e. in the year 2080